The Representation of Religion in Religion Education: Notes from the South African Periphery - Abdulkader Tayob (MDPI AG, 2018)
Scholars of Religion Education (RE) have promoted a non-confessional approach to the teaching of religions that explores and examines the religious history of humankind, with due attention paid to its complexity and plurality. In this promotion, the public representation of religion and its impact on RE has not received sufficient attention. An often hegemonic representation of religion constitutes an important part of religion in public life. Moreover, this article argues that this representation is a phenomenon shared by secular, secularizing, and deeply religious societies. It shows that a Western understanding of secularization has guided dominant RE visions and practices, informed by a particular mode of representation. As an illustration of how education in and representation of religion merges in RE, the article analyses the South African policy document for religion education. While the policy promotes RE as an educational practice, it also makes room for a representation of religion. This article urges that various forms of the representation of religion should be more carefully examined in other contexts, particularly by those who want to promote a non-confessional and pluralistic approach to RE.